PENGARUH SOCIAL SUPPORT TERHADAP TINGKAT RESILIENCE PADA PERAWAT DENGAN SELF EFFICACY SEBAGAI VARIABEL MEDIASI - Aisyah, Siti Nadira; Prawiradilaga, Rizky Suganda; Muhardi, Muhardi (Media Penelitian dan Pengembangan Kesehatan, 2025)
Stress is high in the ER, thus nurses must have the resilience to be able to survive and recover from stressful conditions. Self-efficacy and social support are two factors that may influence resilience. This research examined the link between social support and resilience among ER nurses at RSUD Koja, utilizing self-efficacy as a mediator. This was a quantitative descriptive research utilizing path analysis. A questionnaire adapted from the Connor-Davidson Resilience Scale (CD-RISC), General Self-Efficacy Scale (GSE), and social support questionnaire was used. This research included 59 RSUD Koja’s ER nurses. The sampling method was saturated (total population sampling). The study found a significant positive correlation between social support, self-efficacy, and resilience (p<0.05). Self-efficacy partially mediated the relationship between social support and resilience (p<0.05). Social support mediated by self-efficacy may increase resilience by improving nurses' well-being and confidence in handling obstacles and improving performance, turnover, and hospital image.